Analysis of Three-Dimensional Spatial Selectivity for Rician Channel - Du, Derong; Zeng, Xiaoping; Jian, Xin; Yu, Feng; Miao, Lijuan (Společnost pro radioelektronické inženýrství, 2018)
The spatial selectivity of multipath fading determines the spatial diversity strategy to increase the performance of the communication system. This paper analyses the three-dimensional (3-D) spatial selectivity of Rician channel to strive to alleviate the current lack of analytical studies. A~3-D multipath angular power density (APD) model for Rician channel is proposed. Analytical expressions of the 3-D multipath shape factors are given based on the APD using the multipath shape factors theory. Finally, some important spatial fading statistics like the fading rate variance, level crossing rate (LCR), average fade duration (AFD), spatial correlation and coherence distance are derived, and the analysis on the impact of 3-D spatial angular directions on these spatial fading statistics is presented through simulations. The results would provide useful insight on quantifying and simplifying the analysis and design of the 3-D multiple input multiple output (MIMO) beamforming technology and smart antenna arrays.
Keywords: three-dimensional spatial selectivity; Rician channel; multipath shape factors; angular power density